CERDIK Behavior in Elderly with Hypertension During the COVID-19 Pandemic: Perilaku “CERDIK” Pada Lansia Dengan Hipertensi Selama Pandemi COVID-19 - Kurdi, Fahruddin; Sunaryo, Muhammad Musyafa Fakhurohman; Romadhonia, Firda; Amini, Diah Ayuningrum; Ramadhan, Khoirul (Jurnal Kesehatan Komunitas Indonesia, 2022)
The increasing number of elderly people cannot be separated from health problems. The elderly will experience decreased bodily functions due to physical, psychosocial, cultural, and spiritual changes. Hypertension is a state of abnormally high blood pressure, namely systolic blood pressure above 140 mmHg and diastolic blood pressure above 90 mmHg which is measured at least on three different occasions. Hypertension is a chronic non-communicable disease (PTM) that can gradually reduce the patient's immune system and is very susceptible to infection, one of which is infection with the COVID-19 virus. Hypertension during the COVID-19 pandemic. This type of research is quantitative with a non-hypothetical survey descriptive research design. The population in this study was 20 people with hypertension who live in Sukamakmur Ajung Village, Jember City Regency, using an accidental sample technique. This research tool uses digital tension measurement and CERDIK behavior questions that have been tested for validity (0.635-0.784) and reliability (0.817). The results showed that most had an average age of 64 years, 16 respondents were female, eight did not finish elementary school, and ten respondents worked as laborers. Classification of hypertension stage 1 as many as eight respondents. CERDIK behavior includes: Routine health checks for the majority of 12 respondents, Eliminating cigarette smoke by 14 respondents, Good physical activity by 13 respondents, Good healthy eating patterns by 19 respondents, Good rest by 18 respondents, Good stress management as many as 13 respondents. There needs to be support and monitoring from health workers so that CERDIK behavior can become a culture in treating elderly hypertension.